Pelatihan Canva Sebagai Media Pendukung Pembelajaran Dan Pengembangan Website Pada PKBM Widya Asrama - I Komang Dharmendra; I Gusti Agung Ngurah Rai Semadi; I Made Agus Wirahadi Putra; Gede Adistana Wira Saputra (CV. Multi Kreasi Media, 2024)
The use of technology in education has become an urgent necessity in the digital era. PKBM Widya Asrama, a non-formal educational institution focused on educating local children, currently faces challenges in providing innovative and effective learning support media. Therefore, this community service project aims to provide training in the use of Canva as a learning support tool and to offer guidance on website development. This training is expected to assist PKBM Widya Asrama in enhancing the quality of education they provide and expanding their reach in offering educational access to the surrounding community. In addition to introducing Canva as a tool for creating engaging and creative learning materials, the training will equip the staff and teachers of PKBM Widya Asrama with skills in website development. As a result, the institution can more effectively disseminate information, manage participant data, and communicate their educational programs. Based on the evaluation conducted by the community service team, there has been a noticeable improvement in understanding how to create learning materials using Canva.